Audit Energi Kampus Binus Syahdan - Daryanto Daryanto (Bina Nusantara University, 2012)
Binus as an information technology-based campus, the campus electricity needs swell with the rising costs. Energy crisis threat needs to be observed in order to optimally support the operation of the building. To achieve energy savings on Binus Syahdan, an energy audit needs to be done with strategic measures related to saving HVAC systems, lighting and other utilities. Through observation, evaluation of energy utilization can be practiced to obtain recommendation and implementation of efficient energy management. From the results of energy audits and implementation of energy savings within five months, the saving reaches 33.5% on average each month. Thus Binus can save operating costs, have better work productivity and foster a culture of saving that can be continued for other Binus campuses. Sustainability of this activity is expected to bring Binus as energy-efficient campus pioneer in Indonesia, as a positive response to national energy saving programs.